Humanitarian Logistics: models for the attention of populations affected by natural disasters - Berger Vidal, Esther (2019)
Given the growing trend of the impact of natural disasters, it is necessary to provide immediate help for a certain period of time until the affected population recovers an adequate quality of life. The Humanitarian Logistics, is an approach to serve such populations, through a Supply Chain made up of public and private entities, centralized in Peru by National Institute of Civil Defense, which collects, sends and distributes supplies, doctors and rescuers. The objective is to optimize the help to provide it with eficiency and immediacy. Under the Humanitarian Logistics approach, simulation, inventory and localization models were used to dene the optimal management of supply warehouses and the optimal location of refuges and the risk of ooding in the district of Chosica, case study, was analyzed. As a result, simulation models for inventories and localization have been proposed that generate solutions for diferent scenarios. It is concluded that it is possible to synchronize the aid requirements with the needs in the affected areas keeping the stores supplied at their maximum capacity over time; that with suficient geological information it is possible, by means of location models, to determine safe places of refuge and attention.